Bone Hollow - Ventrella, Kim (Scholastic Press, 2019)
When young Gabe dies in a tornado while trying to save his guardian's beloved chicken, he struggles to understand that he's actually dead. With everyone around him unable to see him, Gabe runs away and encounters a strange girl named Wynne. Alongside his dog, Ollie, Gabe learns the true meaning of death and the role he must play in helping those who are passing from this life into the unknown afterlife.